Comparison of Competitiveness for Crop Estate Commodities in ASEAN and European Markets: Constant Market Share Approach - Lya Aklimawati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Market transition to free trade agreement encourages Indonesia to improveforeign trade performance through stabilization of market position in the internationalmarket. The aims of this research were to analyze the competitivenessof coffee, cocoa, palm oil and rubber products in the international market, andto analyze Indonesia’s export dynamic in ASEAN and European markets. Thisresearch was conducted by analyzing secondary data particularly export datafrom 2010 to 2015. Revealed Comparative Advantage (RCA) and Constant MarketShare (CMS) approaches were used to analyze export competitiveness of Indonesianproducts in the world market. The results showed that Indonesian agriculturalproducts (coffee, cocoa, palm oil and rubber) had a comparative advantage overthe average rate of world (RCA > 1), except natural rubber products. Meanwhile,CMS analysis indicated that dynamic of Indonesian export was more affectedby export growth and product composition effects, than that of market distribution and competitiveness effects. It revealed that Indonesia responded less to market demand in terms of quality, import growth of export destination countries and market intelligence related to competitor market positioning.